The need to improve the formation of the modern academic employment contract - Quinones, Ralph L. [Verfasser] (My University, 1991)
"Faculty policy and procedure manuals are an integral part of academic employment contracts. Yet their importance is underestimated by instructors and educational institutions alike. They are usually referred to in crisis situations only, when the relationship between an educator and a school has begun to deteriorate. It is at this point that faculty allege a violation of their rights and turn to written documentation to support their contention. Colleges and universities, who as the drafters of these documents are thoroughly familiar with their contens, are forced to respond by using the handbooks as shields against legal claims. An acamdic's failure to review faculty manuals at the outset of employment experience leaves himself uniformed as to his rights as an employee and vulnerable to attacks regarding his responsibilities as a professional." (author's abstract) ((en)) Der Beitrag befasst sich mit den Besonderheiten akademischer Arbeitsverträge in den Vereinigten Staaten. Dabei wird insbesondere die Bedeutung der Fakultätshandbücher beleuchtet. Es werden Vorschläge gemacht, wie die Rechte und Verantwortlichkeiten von akademischen Angestellten geregelt werden können. (IAB)
Die Notwendigkeit, die Gestaltung des modernen Arbeitsvertrags mit Akademikern zu verbessern
Keywords: G 1.2.2.1 Lohn- & Tarifsysteme; P 2.6 Hochschulabsolventen; Arbeitsvertrag; Recht; Akademiker; Hochschulrecht; Hochschulpolitik